The Influence of Interest Rates and Exchange Rates on Investment in Indonesia - Hakib, Andi; Sonia, Belinda Girly; Kahar, Kahar (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study aims to analyze the influence of interest rates and exchange rates on investment in Indonesia. A quantitative research approach was employed, utilizing secondary data in the form of time series obtained from the Central Statistics Agency (BPS) and Bank Indonesia for analysis. The data were processed using multiple linear regression analysis, complemented by classical assumption tests and hypothesis testing. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 22. The findings of the study reveal that interest rates have a significant negative effect on investment in Indonesia. This indicates that rising interest rates tend to discourage investment, as the cost of capital becomes more expensive, thereby reducing incentives for both domestic and foreign investors. On the other hand, the exchange rate has a significant positive effect on investment, implying that an appreciation of the domestic currency correlates with increased investment levels. A stronger currency may reduce the cost of imported capital goods and materials, thereby supporting investment growth. These results emphasize the critical role of effective monetary policy in regulating interest rates and maintaining exchange rate stability to foster a conducive investment climate. Policymakers are advised to consider the dynamics between macroeconomic indicators and investment flows in designing sustainable economic strategies. Overall, the study contributes to a deeper understanding of macroeconomic determinants influencing investment behavior in developing economies such as Indonesia.